Comparative thermal inactivation analysis of Aspergillus oryzae and Thiellavia terrestris cutinase: Role of glycosylation. Issue 1 (21st September 2016) - Shirke, Abhijit N.; Su, An; Jones, J. Andrew; Butterfoss, Glenn L.; Koffas, Mattheos A.G.; Kim, Jin Ryoun; Gross, Richard A.
ABSTRACT: Cutinase thermostability is important so that the enzymes can function above the glass transition of what are often rigid polymer substrates. A detailed thermal inactivation analysis was performed for two well‐characterized cutinases, Aspergillus oryzae Cutinase (AoC) and Thiellavia terrestris Cutinase (TtC). Both AoC and TtC are prone to thermal aggregation upon unfolding at high temperature, which was found to be a major reason for irreversible loss of enzyme activity. Our study demonstrates that glycosylation stabilizes TtC expressed in Pichia pastoris by inhibiting its thermal aggregation. Based on the comparative thermal inactivation analyses of non‐glycosylated AoC, glycosylated (TtC‐G), and non‐glycosylated TtC (TtC‐NG), a unified model for thermal inactivation is proposed that accounts for thermal aggregation and may be applicable to other cutinase homologues. Inspired by glycosylated TtC, we successfully employed glycosylation site engineering to inhibit AoC thermal aggregation. Indeed, the inhibition of thermal aggregation by AoC glycosylation was greater than that achieved by conventional use of trehalose under a typical condition. Collectively, this study demonstrates the excellent potential of implementing glycosylation site engineering for thermal aggregation inhibition, which is one of the most common reasons for the irreversible thermal inactivation of cutinases and many proteins. Biotechnol. Bioeng. 2017;114: 63–73. © 2016 Wiley Periodicals, Inc. Abstract : An in‐depth understanding of the thermal inactivation mechanism of proteins provides guidelines for their thermostabilization. Here, Shirke and coworkers proposed a unified model for the thermal inactivation of Cutinases (Polyester hydrolases) based on comparative analysis of homologues. Considering a prominent role aggregation in thermal inactivation of these enzymes, the authors have proposed glycosylation site engineering as a strategy for the inhibition of thermal aggregation which was found to be better than conventional use of trehalose under a typical condition.